Financial Access Improvement For MSME “ Herbal Medicnine Cluster” Through Financial Reporting Assistance - Hani Werdi Apriyanti; Judi Budiman (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Financial access is needed by busines, especially micro, small and medium enterprises (MSMEs). Financial access is able to provide certainty regarding the adequacy of funding for MSMEs. There are several factors that affect financial acces. One of them is the existence of financial information from financial report which relfect the business activities. Financial institutions will usually require the financial report in determining funding decisions. Financial report is a tool that can provide information about the company's performance, as well as information related to the company's cash flow. Financial reports is needed for prospective creditors to get an overview of business activities during one reporting period, and business prospects in the future. Financial report can provide information needed by prospective creditors as a basis for consideration in funding decisions. Not all micro, small and medium enterprises have the ability to prepare financial reports. Business actors who are members of the MSME group have the same problem, namely not being able to compile financial reports. This condition can hinder business actors from accessing finance. Business actors will find it difficult to get access to the capital needed for business development. Therefore, training and assistance programs in the preparation of financial reports are needed for business actors. This program aims to provide an understanding related to the importance of financial statements, the benefits of financial statements for businesses, and to train the ability of business actors in preparing financial reports.